Estimation of total flux of polycyclic aromatic hydrocarbons facilitated by methane ebullition into water column from global lake sediments. (1st October 2021) - Sun, Tingting; Li, Wenxuan; Yin, Ke
Highlights: Methane ebullition significantly enhance PAH flux into water from lakes sediments. Methane ebullition facilitated PAH flux offsets 52–118% of PAH by dry deposition. PAH flux rises with time due to enhanced gas ebullition and continuous PAH emission. Abstract: Methane ebullition and contamination are two typical characteristics from lakes, however, these two are generally studied independently. In fact, the exchange of matter and energy between methane bubbles and their surrounding environment can be very active to enhance the contaminant transport. There is limited research on understanding the characteristics and trends of gas ebullition facilitated contaminant emissions in large areas considering water and air as receptors. We herein estimate the transport capacity of methane ebullition for polycyclic aromatic hydrocarbons (PAHs) out of the sediment from global lakes, which may reach an average of 71 (up to 159) t yr −1 . Methane bubbles could transfer one third of the total PAH flux from sediments, or equivalent of 1.3–3.0 ng L −1 of additional PAHs, into the water column with the rest going into air, offsetting from 52 to 118% of dry PAH deposition flux into global lakes sediment per year. Given the PAH concentration in lake water is often in the range of 0.1–100 ng L −1, ebullition facilitated PAH flux may increase PAH concentration by a factor of 1.4 to 2.4 until 2, 100, being a significant contributor for the PAH increment in lake waters.